Historical and Economics Studies of Aceh-Deli Railroad System - Usman; Muhammad, Said; Ibrahim, Husaini; Musnadi, Said (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to historically, politically, and economically investigate the Aceh-Deli Indonesia railway. This research employed the critical historical methodology. According to Gottschalk (1975: 18), when examining a critical historical method, the subtance is to exclude unauthentic materials and to conclude reliable testimonies concerning the authentic materials. The Aceh-Deli railway had a major impact on the alteration and movements of politics and religion, which is the workers employed in both railway and plantation companies in the Dutch East Indies, with treatment as "Contract Labour" causing protests from the political circles in the European Parliament; Douwes Dekker and Van Deventer fought for the fate of the indigenous population. The originality of this research seems from the Historical and Economics Comparative Studies of Aceh-Deli Railroad System. Up to now, there has been no detailed study of the Aceh-Deli Railroad System (Historical and Economic Studies of 1876-1942).